International Entrepreneurial Culture in the Tunisian Context - Soufien Zouari (Research Synergy Foundation, 2024)
The increasing internationalization of companies has led us to reflect on the structuring of an emerging field of research, namely international entrepreneurial culture (IEC). Moreover, the absence of a solid theoretical framework is one of the main factors contributing to the scattered nature of research in this field, which has led us to conduct further research on international entrepreneurial culture. After presenting the definition and dimensions of IEC, this study aims to analyze and synthesize previous empirical findings on this phenomenon to understand its causes and influencing factors, behaviors, and processes in the global context in which it is embedded. Following this study in the Tunisian context, we found that Tunisian companies have no intention of embracing the phenomenon of international entrepreneurial culture. The absence of an organizational culture, whether among managers or members of the organization, has a major effect on the entrenchment of an international entrepreneurial culture. Thus, international trade is a real motivator for Tunisian companies to embark on internationalization. In this respect, we propose some avenues of research to consolidate and develop the field of international entrepreneurial culture.